Síntesis y caracterización de pentóxido de vanadio y niobio (2024)
This research presents the synthesis of five samples of vanadium pentoxide (V2O5) which contains reduced graphene oxide (rGO) and different doping percentages of niobium pentoxide (Nb2O5) by means of hydrothermal technique, incorporating two or more compounds seeks to estimate the microstructure, chemical composition and vibrational modes of synthesized samples. Thus, with the support of X-ray Diffraction (X-ray Diffraction), Raman Spectroscopy and Scanning Electron Microscopy (SEM) equipment, crystalline structures, indications of a well-defined crystalline network and formation of agglomerated and dispersed nanoparticles were found.